Recent Advances in Intermolecular Hydroacylation of Alkenes with Aldehydes through Rhodium Catalysis - Guo, Rui; Zhang, Guozhu (Synlett, 2018)
The rhodium-catalyzed intermolecular hydroacylation of alkenes with aldehydes is an atom-economical method for the synthesis of ketones. Here, we give a brief review on its development and we highlight recent advances in chelating strategies for the stabilization of acyl rhodium species by coordinative saturation.
Keywords: rhodium catalysis; hydroacylation; alkenes; aldehydes; chelation; coordinative saturation